A reflection on higher education in health in the context of the COVID-19 pandemic: traditional education still perpetuates (Research, Society and Development, 2022)
Pandemics that occurred in the past strongly marked all areas and spheres that makeup society. This gave rise to important and revolutionary events with repercussions that continue to this day. The COVID-19 pandemic was no different in this regard, especially as it emerged in an extremely globalized age. Therefore, the objective of this critical review was to reflect on higher health education in the context of the COVID-19 pandemic, with a focus on traditional education that is perpetuated through the new context. There were many challenges faced by this new reality, especially regarding the use of technology to provide quality education. However, we believe that one of the greatest challenges of education in this context continues to be overcoming traditional teaching, which has been subtly perpetuated in many institutions of higher education in health. We should discuss and reflect more on the camouflage of current teaching: the intentional camouflage driven by political and doctrinal interests; and the involuntary that drags from generation to generation.